Targeting Molecular Inflammatory Pathways in Granuloma as Host-Directed Therapies for Tuberculosis - Guler, Reto; Ozturk, Mumin; Sabeel, Solima; Motaung, Bongani; Parihar, Suraj P.; Thienemann, Friedrich; Brombacher, Frank (Frontiers in Immunology, 2021)
Globally, more than 10 million people developed active tuberculosis (TB), with 1.4 million deaths in 2020. In addition, the emergence of drug-resistant strains in many regions of the world threatens national TB control programs. This requires an understanding of host-pathogen interactions and finding novel treatments including host-directed therapies (HDTs) is of utter importance to tackle the TB epidemic. Mycobacterium tuberculosis (Mtb), the causative agent for TB, mainly infects the lungs causing inflammatory processes leading to immune activation and the development and formation of granulomas. During TB disease progression, the mononuclear inflammatory cell infiltrates which form the central structure of granulomas undergo cellular changes to form epithelioid cells, multinucleated giant cells and foamy macrophages. Granulomas further contain neutrophils, NK cells, dendritic cells and an outer layer composed of T and B lymphocytes and fibroblasts. This complex granulomatous host response can be modulated by Mtb to induce pathological changes damaging host lung tissues ultimately benefiting the persistence and survival of Mtb within host macrophages. The development of cavities is likely to enhance inter-host transmission and caseum could facilitate the dissemination of Mtb to other organs inducing disease progression. This review explores host targets and molecular pathways in the inflammatory granuloma host immune response that may be beneficial as target candidates for HDTs against TB.